PENGARUH LINGKUNGAN BELAJAR TERHADAP MOTIVASI DAN KETERAMPILAN PRAKTIK SISWA DI SMK MA'ARIF NU 1 BENER - Puput Ardhianto; Dwi Jatmoko; Widiyatmoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the condition of the student learning environment, the level of student learning motivation, and the effect of the learning environment on the learning motivation and practical skills of class XI Light Vehicle Body Engineering (TBKR) students at SMK Ma'arif NU 1 Bener. The method used in this study is a quantitative method with descriptive and inferential approaches. The population in this study were all class XI TBKR students, with a sample of 30 students. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis techniques include descriptive tests, normality tests, linearity tests, and hypothesis testing using regression analysis and t-tests. The results showed that the student learning environment was in the very good category, student learning motivation was in the very good category, and there was a positive and significant influence between the learning environment on student learning motivation and practical skills. This is evidenced by correlation coefficient values of 0.781 and 0.483 and significance values of 0.000 and 0.004 (< 0.05). In addition, the contribution of the learning environment to learning motivation was 61% and to practical skills was 23.3%.